Utilization and clinical outcomes of kidney transplants from deceased donors with albuminuria in the UK: a national cohort study. Issue 11 (6th September 2022) - Greenhall, George H B; Robb, Matthew; Johnson, Rachel J; Ibrahim, Maria; Hilton, Rachel; Tomlinson, Laurie A; Callaghan, Chris J; Watson, Christopher J E
ABSTRACT: Background: Urinalysis is a standard component of potential deceased kidney donor assessment in the UK. The value of albuminuria as a biomarker for organ quality is uncertain. We examined the relationship between deceased donor albuminuria and kidney utilization, survival and function. Methods: We performed a national cohort study on adult deceased donors and kidney transplant recipients between 2016 and 2020, using data from the UK Transplant Registry. We examined the influence of donor albuminuria, defined as ≥2+ on dipstick testing, on kidney utilization, early graft function, graft failure and estimated glomerular filtration rate (eGFR). Results: Eighteen percent (1681/9309) of consented donors had albuminuria. After adjustment for confounders, kidneys from donors with albuminuria were less likely to be accepted for transplantation (74% versus 82%; odds ratio 0.70, 95% confidence interval 0.61 to 0.81). Of 9834 kidney transplants included in our study, 1550 (16%) came from donors with albuminuria. After a median follow-up of 2 years, 8% (118/1550) and 9% (706/8284) of transplants from donors with and without albuminuria failed, respectively. There was no association between donor albuminuria and graft failure (hazard ratio 0.91, 95% confidence interval 0.74 to 1.11). There was also no association with delayed graft function, patient survival or eGFR at 1 or 3 years. Conclusions: Our study suggests reluctance in the UK to utilize kidneys from deceased donors with dipstick albuminuria but no evidence of an association with graft survival or function. This may represent a potential to expand organ utilization without negatively impacting transplant outcomes.